The interpretation of the New Testament as the study of texts and contexts: hermeneutics, identities, communities - Punt, J. (Faculty of Theology, University of the Free State, 2013)
The focus here is on texts, Pauline and texts invoked by Paul, and ever-present imperial "super"-texts. The latter also establishes the context, as the social setting of Paul's letters with their rhetorical use of Othering was the Roman Empire with its identity politics. The rhetorical power of Paul and his scriptural texts contributed to discursive formations, since a strong sense of being and identity was negotiated through these texts, even when admitting that such formations are always in process, mutating and reformatting. Construing notions of Others was a particularly important feature in defining boundaries, for generating insiders and outsiders in Pauline texts.
Keywords: Social location; Identity; Memory; Empire; Galatians